Organic chemistry. - Mehta, Bhupinder, ....-; Mehta, Manju, ....- (New Delhi : PHI Learning, 2011)
This newest title in Barron's College Review Series will serve students as a helpful supplement to their main textbook in organic chemistry. It also makes a valuable review book for students who are preparing to take standardized tests that require knowledge of organic chemistry-for instance, the Medical College or Pharmacy College Admission Tests. The author presents a broad overview of subject material, defines key terms, and summarizes organic chemisty reactions and reaction mechanisms